The preventive prison and international law - Colunge Villacorta, Jorge (2020)
The article focuses on the phenomenon of pre-trial detention abuse in the Latin American region, mainly in light of the American Convention on Human Rights and the UN Pact on the same subject, analyzing the legal currents on its application and its consequences in the Peruvian legislation, concluding in the formulation of recommendations.